MENUJU PENYATUAN KALENDER HIJRIYAH - Bashori Alwi (MAQASHID, 2020)
Differences in determining the timing of worship seem to be a matter of course, because too often in this country there are differences in the determination of worship, especially in the implementation of the fasting month of Ramadan, Eid al-Fitr, Eid al-Adha and others, this is because there is no agreement related to it. a fixed calendar, so that Muslims in Indonesia do not yet have an established Hijriyah calendar that can be used as a common reference. The determination of the beginning of the month of Qamariyah is indeed a matter of ijtihadiyah because there is no single argument either from the Koran or as-Sunnah which explains in detail about the method or method of determining the beginning of the month of Qamariyah, so that many scholars have different opinions in interpreting how to determine the first day of the month Qamariyah. Also the results of astronomical calculations which some scholars say as definite or qoth'i, also reaped many versions so that they could not convince the people to make it the only method of determination. So the results of this study conclude that in order to realize the unification of the determination of the beginning of the month there must be one school that becomes the authority, namely the state madzhab, as in the rule of "the decision of the judge (State) to erase differences".